Characterization of oleanolic acid derivative for colon cancer targeting with positron emission tomography. (April 2014) - Kim, Sung-Min; Jeong, Il Ha; Yim, Min Su; Chae, Min Kyung; Kim, Hak Nam; Kim, Dong Kue; Kang, Choong Mo; Choe, Yearn Seong; Lee, Chulhyun; Ryu, Eun Kyoung
Abstract Oleanolic acid (OA) is a pentacyclic triterpenoid found in various plant species. Triterpenoid compounds have been shown to inhibit tumor proliferation and to induce apoptosis in cancer cells. We synthesized an OA derivative and evaluated its inhibitory effects on cell proliferation in human colon cancer. Radioisotope-labeled OA was prepared for noninvasive monitoring of tumor progression in vitro and in vivo. The OA derivative decreased cell survival in a concentration-dependent manner and increased apoptosis in HT-29 cells. Furthermore, it induced downregulation of cyclin D1, Cox-2, Bcl-2 and Bcl-xL mRNA expression and upregulation of the mRNA expression of the anti-apoptotic Bax protein in HT29 cells. NF-κB p65 and IκB expression also decreased, whereas expression of the apoptosis marker, the cleaved form of PARP-1, significantly increased in OA derivative-treated HT-29 cells. Radioisotope-labeled OA (68Ga-NOTA-OA) showed significantly high tumor uptake, as assessed by biodistribution and positron emission tomography imaging analyses, at 1 h post-injection in the human colon cancer xenograft model. Our results demonstrate that the OA derivative has promising properties as an anticancer drug and as an imaging tool for tumor targeting.